KARAKTERISTIK KIMIA DAN ORGANOLEPTIK CAKE DARI BERBAGAI KONSENTRASI BUAH KELOR MUDA (Moringa oleifera Lamk.) - Veronika, Veronika; Rahmatu, Rostiati; Kadir, Syahraeni (AGROTEKBIS, 2019)
Utilization of Moringa is still not well known, normally known as one of the veggie menu. In addition to direct consumption in fresh form, Moringa can also be processed into powder form that can be used as a base material for food products, such as processed cakes,biscuits and other processed. This study aims to determine the concentration of Moringa fruit juice that gives the best effect against chemical and organoleptic properties cake. The research was conducted from January to March 2018 in the Laboratory of Agro-Industry, Faculty of Agriculture, University,of Tadulako. Research using completely randomized design (CRD) and a randomized block design (RBD) the factors which consist of 5 level of concentration, ie 37,5%, 41,1%, 44,4%, 47,3% and 50% were repeated 3 times so that obtained 15 experimental units. Treatment significantly or very real then tested further using honestly significant difference test (HSD) level of 5% or 1%. The results showed that the chemical and organoleptic characteristics of the best there is on the cake with a concentration of moringa juice 50%, with a content of 29.84% moisture, 7.79% protein content, fat content of 23.52%, 0.60% fiber content.